(3eLehYI CTYGQs
(3ChdgG (B:s
(3ddSjO GdSfO TQja GdcGXej, QMeg Gddg(B: (3fXQJ aCRQJ HGdZRGd GdCMhQ hSWJ aCRQJ cd djmK bShQ s
(3BNQgG (B:s
(3dh TGA jeOoM HGdPj gh Cgdg MUQ GdCfGe aeG SeYJ fTjOG s
(3GdfSNI HgG MhGTs
(3Ydi gGeTgG TQhM hJYdjbGJs
(3hHgG fXGe GdJYbjHIs
(3hge GdTQja Hf adGM GdcGXej, hGdSjO EHQGgje hGdSjO CMeO GdWGgQ, hMSf Hf eMeO Hf Ydj GdOeSJGfj, hgGTe GdcYHj, hBd GdfMhj, hZjQge s
(3hGdSjO EHQGgje hGdSjO CMeO GdWGgQs
(3GdJhKjbGJ GdeQLYjI (B:s
Keywords: (3GdCOHs